Tingkat Kinerja Penyuluh Pertanian di Kabupaten Ogan Komering Ulu (OKU) Selatan - Hernanda, Tiara Aprilia; Fatchiya, Anna; Sarma, Ma'mun (Jurnal Penyuluhan, 2015)
The existence of professional agri-extension worker is main extension’s issue to move it effectively and efficiently. Professionalism related with agri-extension worker’s performance. The existing main problem is agri-extension worker’s performance in Indonesia is quite low. It is because of agri-extension worker has low individual quality, include in some district in South Sumatera. Therefore, the objectives of this study is to measure the performance of agri-extension worker. The research used a survey method with quantitative and qualitative approach. It conducted in South Ogan Komering Ulu (OKU) District, South Sumatera Province, with census method to sampling. The respondents of the study were 65 of agri-extension workers. The scoring method used the measurement indicators from The Regulation of Minister of Agriculture Number. 91/Permentan/OT.140/9/2013. Overall performance of agricultural extension agents in South OKU District is in well category. It is supported by the worker’s ability to prepare and implement extension’s activities. However, there are shortcomings in terms of extension’s evaluation had been done. Thus, it is required a continuous evaluation. Keywords: extension performance, extension, extension worker